An Adaptive Power level Allocation Model in LoRa for Internet of Things - Kumari P.; Gupta H.P.; Dutta T. (My University, 2025)
Internet of Things (IoT) finds their applications in many areas that include environmental monitoring, industrial control, traffic congestion control, smart metering, and smart parking. An important issue of research in IoT is to successfully transmit the data to the cloud and yet minimize the energy consumption of the battery-powered IoT devices. Long Range (LoRa) is a long-range wireless communication protocol that competes against other low-power wide-area networks. In this paper, we propose a Stackelberg Game based model for allocation of the appropriate power levels to the LoRa nodes in energy-efficient LoRa network. The utility of the network server, works as a leader player, is to successfully receive the data from the LoRa nodes. The utility of the LoRa nodes, work as followers player, is to reduce the power consumption during transmission of the data to the LoRa gateway. Simulation results evaluate the performance of the proposed game model to validate its effectiveness. © 2019 IEEE.